Prontuário Eletrônico de Pacientes (PEP): políticas e requisitos necessários à implantação no Hospital Universitário de Santa Maria (HUSM) - Cruz, Jorge Alberto Soares (2011)
This research related the implications of the deployment and use of Electronic Patients Record at University Hospital of Santa Maria, and his involvement with the archives science principles and concepts. This is justified by the presumption that the theoretical models existing are devoid of theoretical and archival authenticity and reliability. The focus of this study was grounded on objectives that intertwine and complement: strategies that include aspects of preservation of electronic documents and their relationship with the authenticity and reliability of the information, the study and analysis of some models of software for PEP, which was a parallel track with the current legislation, presentation of a metadata schema with potential for use in PEP, from the analysis and study of e-Arqu Brasil, a study of PEP as memory and cultural heritage. A qualitative research was applied, and was used a compound of issues related to the objectives, too. The results are founded on the principle that all archival work should be related to reality documentary that is known through the collection of information essential to the development of a scientific investigation. It was possible to verify the absence of involvement of archivists in the implementation and development of a PEP system, a difficult task that requires capability and technical skills of professionals and intellectuals engaged. It is concluded by advocating the PEP with the document archive for permanent preservation, and as an object of study for professionals in health, information technology, historians, sociologists and archivists.